(untitled) (Comprehensive Journal of Science, 2026)
This study aimed to measure the level of financial inclusion through its indicators access to francial services, use of financial services. and quality of financial servicesl, as well as to measure the level of competitive advantage. The study also aimed to measure the expected impact of financial inclusion indicators on the competitive advantage of Libyan commercial banks, applied to the United Bank for Trade and Investment. The study sample consisted of bank employees in the head office (Tripoli) and branches in the western region A questionnaire was used as the data collection tool. It was designed to align with the nature of the study and to achieve its objectives. The questionnaire was divided into three sections covering all aspects of the research problem. The first section was dedicated to personal data, the second section was designed to cover financial inclusion indicators, and the third section was for the dependent variable, which is competitive advantage. The researcher adopted the descriptive approach. To achieve the objectives and test the hypotheses. appropriate statistical analyses were conducted using the Jamovi statistical software. The study reached several conclusions, the most important of which are: 1-The level of financial inclusion in the bank under study was high. The indicator for the use of financial services had the highest percentage among the financial inclusion indicators, followed by the indicator for the quality of financial services, and then the indicator for access to financial services. 2- The level of competitive advantage was also high, as there is a strong positive relationship between financial inclusion indicators 3-Then we no statisticaly significant differences in the responses of the study sample attributablets demographic variables. However, there are statistically significant differences in the responses of the study saniple ngarding the impact of financial inclusion indicatons on enhancing competitive advantage, attributable to the variable of financial inclusion training. Based on the above results, the following recommendations were proposed for the bank under study 1-Expanding the provision of digital services by malementing the Egypt oppication to reduce customer visits to branches. It is also recommended for the geographical spread of the bank’s branches.-Training employees by launching training works90-=p;’0hops on the importance of financial inclusion. 3-It is also recommended to creste educational programs for customers on how to use internet applications to benefit from digital financial services